Analysis of Language Errors in Journal Writing of Students Physics Studies Program, Medan State University - Alexander Pasaribu; Hanna Tasya Siahaan; Imel Simbolon; Rindi Ani Lumban Gaol; Lasenna Siallagan (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2024)
The aim of this research is to evaluate errors in writing scientific papers of FMIPA students studying Indonesian at Medan State University. Error analysis and the use of standard and correct language are the main theories in studying research problems. Descriptive-qualitative method is used. The results showed that the errors consisted of spelling, grammar and systematic errors. Spelling errors include capital and lowercase letters and italics; use of inappropriate and incomplete words; and the use of passive verbs that are confused with the function of prefixes as prepositions. Systematic errors include incomplete paragraphs and sentences.